Hibridisasi Ritus Tradisional sebagai Media Komunikasi Pembangunan di Kecamatan Cempa Kabupaten Pinrang - Andi Muhammad Agriawan Suryaalim; Sarwititi Sarwoprasodjo; Riko Bintari Pertamasari (Jurnal Komunikasi Pembangunan, 2018)
This study aimed to analyze the dynamics of hybridization results in conventional extension and the traditional rites(especially the ceremony of down to rice field), hybridization requirements, and potential benefits for communication development. The research was conducted in two rice farming communities in Cempa Sub-district, Pinrang District, South Sulawesi Province. The research method used is the ethnography of communication with the taking of data through observation and in-depth interview. Activities observed in this research, namely Rembuk Madya, Tudang Sipulung, and Mappalili (ritual ceremony). In-depth interviews were conducted on 10 purposely selected informants, consisting ofextension officers, traditional leaders, leaders of peasant organizations, and farmers. The results indicate dynamics on hybridization practices in the three activities. These differences are based on communication objectives and participants' information needs. The conditions of hybridization can be categorized based on the internal conditions of the community and community relations with the government. Hybridization in the practice of extension and tradition rites is beneficial for maintaining social capacity, as well as increasing the participation of local farmers in agricultural development programs.